2007
DOI: 10.1093/aob/mcm062
|View full text |Cite
|
Sign up to set email alerts
|

Benzylaminopurine Application on Two Different Apple Cultivars (Malus domestica) Displays New and Unexpected Fruitlet Abscission Features

Abstract: BA probably exerts its thinning effect through vegetative growth. In the 'spur' type 'Red Delicious' the chemical is ineffective, probably due to a limited action on shoot growth due to genetic characteristics. The amount of MdACO1 transcripts in seeds is a good indicator of abscission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 17 publications
6
16
0
Order By: Relevance
“…The increasing expression of the genes coding for ET biosynthesis enzymes, the increase in the ACC content, as well as studies of ACC immunolocalization in the abscission zone, all suggest that ethylene is directly involved in the functioning of the flower abscission zone in L. luteus. This hypothesis was also confirmed by the results of research performed in other plant species, in which the factors activating abscission of particular organs stimulate the expression of both ACC synthases and oxidases, e.g., in apple (MdACO3, MdACO4, MdACO1) or tomato (SlACO5, LACS2) [41][42][43][44]. Moreover, it was found that immediately before flower abscission in Ecballium elaterum and S. lycopersicum [45,46], the ethylene production rate increases.…”
Section: Discussionsupporting
confidence: 61%
“…The increasing expression of the genes coding for ET biosynthesis enzymes, the increase in the ACC content, as well as studies of ACC immunolocalization in the abscission zone, all suggest that ethylene is directly involved in the functioning of the flower abscission zone in L. luteus. This hypothesis was also confirmed by the results of research performed in other plant species, in which the factors activating abscission of particular organs stimulate the expression of both ACC synthases and oxidases, e.g., in apple (MdACO3, MdACO4, MdACO1) or tomato (SlACO5, LACS2) [41][42][43][44]. Moreover, it was found that immediately before flower abscission in Ecballium elaterum and S. lycopersicum [45,46], the ethylene production rate increases.…”
Section: Discussionsupporting
confidence: 61%
“…The chemical thinners may be consisted of various chemical compounds, but the application of plant growth regulators and some insecticides are of preference in this regard (Reyes et al, 2008). The mode of action of the chemical thinners may be varied like ethephon and carbaryl chemicals normally effect and alter the hormonal status of the fruitlets while some chemicals like auxin and cytokinin (PGRs) exhibit their effect on whole plant not just limited to flower or fruitlets (Bangerth, 2000;Cin et al, 2007;Wertheim, 2000). However, the use of chemical thinners in inappropriate application time, dosage or without knowing the cultivar response, often resulted in yield reduction (Stopar and Lokar, 2003;Esitken et al, 2009;Milić et al, 2012), decreased fruit growth and fruit russeting Weibel et al, 2012;Stopar et al, 2007a;Milić et al 2012), poor colouration of fruits (Byers and Carbaugh, 1991;Wertheim, 2000) and sometimes resulted in lowering the Ca concentrations in fruits (Elfving and Cline, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to further decrease the production costs for the growers, a genetic approach which would exploit natural variation of the germplasm is of primary importance [6]. In order to optimize the discovery of traits interesting for a specific fruit load, which would give the best economic value, the study of the abscission physiology in the different cultivars is a must [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Fruitlet abscission in apple (Malus × domestica L. Borkh) occurs in a period of competition between reproductive and vegetative parts and among fruitlets [7]. This competition is due to several factors [8,10,11]. Hormones play a central role in modulating abscission as can be proven by the fact that bioregulators are widely used to thin excess fruitlet load [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation